Age-related changes of elements in human olfactory bulbs and tracts and relationships among their contents - Lining Ke (2018)
To elucidate compositional changes of the olfactory bulb and tract with aging, the authors investigated age-related changes of elements in the olfactory bulbs and tracts of Japanese and the relationships among the elements. After ordinary dissection at Nara Medical University was finished, the olfactory bulbs were resected with the olfactory tracts from 40 subjects. The subjects consisted of 15 men and 25 women, ranging in age from 65 to 102 years (average age∈=∈84.6∈±∈7.5 years). After ashing with nitric acid and perchloric acid, element contents in the olfactory bulbs and tracts were analyzed by inductively coupled plasma-atomic emission spectrometry. Seven elements of Ca, P, S, Mg, Zn, Fe, and Na did not change significantly in the olfactory bulbs and tracts with aging. The Ca, P, and S contents of major elements were less than 10 mg/g in all of the olfactory bulbs and tracts. Regarding the relationships among the elements, extremely or very significant direct correlations were found among the contents of Ca, P, Mg, Zn, and Na in the olfactory bulbs and tracts, with one exception. In addition, an extremely significant direct correlation was found between S and Mg contents and a very significant direct correlation was found between P and S contents. As P increased in the olfactory bulb and tract, Ca, Mg, Zn, Na, and S also increased in the olfactory bulb and tract. © 2008 Humana Press Inc.